Outcomes of protocol-based management for venoarterial extracorporeal membrane oxygenation in congenital heart surgery - A 2-decade experience - Moses Othin; Maruti Haranal; Sivakumar Sivalingam; Khairul Faizah Mohd Khalid; Kok Wai Soo (Wolters Kluwer Medknow Publications, 2024)
Background Extracorporeal membrane oxygenation (ECMO) is a vital mechanical circulatory support used with increasing frequency in complex congenital cardiac surgeries. This study evaluated the outcomes of a protocol-based venoarterial (VA) ECMO program following congenital heart surgeries. Methods and Results This was a retrospective review of 198 patients who underwent VA-ECMO after congenital cardiac surgeries at our institute between 2004 and 2023. Patients were divided into pre-ECMO protocol (2004-2017) and post-ECMO protocol (2018-2023) implementation. There were 107 patients in the preprotocol era and 91 in the postprotocol era. We compared weaning from ECMO and survival to hospital discharge between the two eras. An analysis of the factors influencing survival to hospital discharge was also done. ECMO was initiated through the central cannulation technique through median sternotomy in all patients. The median age and weight at initiation were 4 months (interquartile range [IQR] 1-33.5 months) and 4.4 kg (IQR 3.3-10.1 kg), respectively. The successful weaning of the ECMO (n = 67/91, 73.6%) and survival to discharge (n = 43/91, 47.3%) were higher in patients of the postprotocol era. However, it was not statistically significant. Higher risk adjustment for congenital heart surgery-1 >3 and acute kidney injury were independent predictors of poorer survival to hospital discharge. Conclusions A protocol-based ECMO program may improve outcomes of successful weaning and survival to discharge in patients undergoing congenital cardiac surgeries.